Effect of fermentation duration on microstructure and quality of acha flour and its cookies acceptability - Sunday Samuel Sobowale; Benjamin Oluwole Omotoso; Joy Ikedichi Agbawodike (npj Science of Food)
Abstract This study investigated the effect of fermentation durations (24,48 and 72 h) on the microstructure and nutritional quality of acha flour and resultant cookies. Results showed that there were significant differences (p < 0.05) in the functional and pasting properties of the flour and cookies samples. As increase in fermentation duration resulted increases in oil absorption capacity and dispersibility of the samples. The protein content of the fermented samples showed slight increase from 8.83 to 9.33%. There was significant difference (p < 0.05) in the all the minerals element. The Fourier transform infrared (FTIR) spectra increased the band intensities (3860–3650 cm− 1). XRD patterns revealed slightly higher crystallinity, with A-type for flour and V-type for cookies. SEM revealed a shift from irregular compact grains to a regular, loose structure. Sensory tests affirmed that fermented acha flour holds promise for various food applications, including complementary foods, and gel formulations with reduced syneresis.